CAVEATS OF PROSTATE CANCER DIAGNOSIS: DIAGNOSTIC UTILITY STUDY OF DIGITAL RECTAL EXAMINATION, PROSTATE VOLUME AND PROSTATE SPECIFIC ANTIGEN - Rehman, Ashfaq Ur; Khattak, Ikram Ullah; Jan, Mir Alam; Ahmad, Bilal (Journal of Postgraduate Medical Institute, 2018)
Objective: To investigate the diagnostic utility of prostate specific antigen (PSA), digital rectal examination (DRE) and prostate volume (PV) in arriving at diagnosis of prostate cancer (PCa) in a cohort of elderly male patients present- ing with lower urinary tract symptoms (LUTS). Methodology: This was a descriptive study of 120 elderly (> 50-years-old) male patients who presented with complaints of LUTS or were referred for fur- ther specialist management. All patients were s subjected to DRE on clinical examination, PV assessment on ultrasonography and a PSA screen. Prostate biopsy reports were recorded (positive or negative for PCa) once the patient underwent prostatectomy (transvesical prostatectomy-TVP, transurethral re- section of prostate-TURP or transrectal prostate biopsy-TRPB). Results: There were 120 patients with overall mean age of 71.03 ±9.19 years. Combining the three test variables, namely DRE, PV and PSA, the sensitivity was 61.8%, specificity was 70.8%, positive predictive value was 64.1% and negative predictive value was 68.7%. The most effective single test was DRE if applied alone, and the most ineffective was PSA if considered alone for diagnosing PCa. Patients with a positive DRE had 5.45 while raised PSA had 1.01 times higher odds to exhibit PCa as those having a negative DRE or a lower PSA. However, an increasing PV had no significant effect on the likelihood (OR =0.96, 95% CI, 0.928 to 1.008) of having a diagnosis of PCa. Conclusion: A combination of the DRE, PV and PSA has good diagnostic capac- ity and should be used to better identify prostate cancer patients.